4D Biofabrication: 3D Cell Patterning Using Shape‐Changing Films. (18th January 2018) - Stroganov, Vladislav; Pant, Jitendra; Stoychev, Georgi; Janke, Andreas; Jehnichen, Dieter; Fery, Andreas; Handa, Hitesh; Ionov, Leonid
Abstract: A novel approach for fabrication of 3D cellular structures using new thermosensitive shape‐changing polymer films with photolithographically patterned surface—4D biofabrication is reported. The surface of shape‐changing polymer films is patterned to selectively adsorb cells in specific regions. The 2D cell pattern is converted to the 3D cell structure after temperature‐induced folding of the polymer films. This approach has a great potential in the field of tissue engineering and bioscaffolds fabrication. Abstract : A new way to achieve selective cell adhesion to a surface in 3D space is shown . The material being used is a self‐folding thermoresponsive polymer bilayer with patterned surface. Pattern on the surface governs where cells will adhere and thermoinduced folding creates a 3D shape filled with cells.